In Vitro Fertilization: Trends, Criticism and Challenges - Ige Busayo Sarah; Risikat Idowu Fadare; Oluwaseyi Abiodun Akpor (RGUHS Journal of Nursing Sciences)
Assisted Reproductive Technology ART frequently uses in vitro fertilization IVF a sophisticated method of treating infertility in which a donor or non-donor ovum is fertilized in a laboratory using either donor sperm or spouses semen. IVF can employ donor sperm and owner partner sperm donor sperm and donor ovum donated embryos and patient ovum and partner sperm depending on the kind of infertility. An increasing number of people are now having IVF procedures because of the convergence of supply driven by new technology and increased demand brought about by sociodemographic changes. An increase in the use of IVF is being driven by shifting societal standards and demographics. Because of its higher success rate in vitro fertilization has emerged as the gold standard for treating infertility. However there are a number of challenges and criticisms surrounding this procedure which deters some people from using it as a cure for infertility